On the male of the orb weaving spider Micrathena cyanospina (Lucas, 1835) (Araneidae, Araneae) - Nogueira, André A.; Brescovit, Antonio D. (Zootaxa, 2011)
Most species of spiders exhibit some degree sexual size dimorphism (SSD). Females are usually larger than males, about 20% on average (Vollrath 1998), although this difference can be much larger. By convention, species in which the adult males are half or less of the adult female size are considered sexually dimorphic, some representing cases of extreme SSD (Hormiga et al. 2000). It is worth mentioning that although males are called dwarfs, large SSD is often a consequence of female gigantism rather than male dwarfism (Hormiga et al. 2000).